1998
DOI: 10.1007/s004050050037
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation after subtotal petrosectomies

Abstract: Among cochlear implant candidates there are patients who have abnormal middle and/or inner-ear conditions that make them unsuitable for implantation. Insertion of a foreign body may also be contraindicated in the setting of an existing or potential intracranial communication, or when the ear is prone to infection. Five patients presented with such unfavorable conditions. These included a Mondini dysplasia with persistent cerebrospinal fluid leak, an atretic mastoid with meningocele, chronic otitis media, a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 17 publications
0
58
0
4
Order By: Relevance
“…The main concern of standard obliterative procedures is the risk of residual or recurrent cholesteatoma. For this reason, surgeons performing obliterative operations recommend a two-stage procedure if a cholesteatoma is present or if there is any doubt about removal of the squamous epithelium (Bendet et al, 1998;Gray et al, 1999). Colletti et al (1999) suggested cochlear implant insertion via a middle cranial fossa approach, although this may be considered by other surgeons as overtreatment with potential serious complications.…”
Section: Chronic Otitis Mediamentioning
confidence: 98%
“…The main concern of standard obliterative procedures is the risk of residual or recurrent cholesteatoma. For this reason, surgeons performing obliterative operations recommend a two-stage procedure if a cholesteatoma is present or if there is any doubt about removal of the squamous epithelium (Bendet et al, 1998;Gray et al, 1999). Colletti et al (1999) suggested cochlear implant insertion via a middle cranial fossa approach, although this may be considered by other surgeons as overtreatment with potential serious complications.…”
Section: Chronic Otitis Mediamentioning
confidence: 98%
“…Intraoperative lumbar drainage has also been used to effectively control the gusher and kept in postoperative period [17,20]. Subtotal petrosectomy with isolation and obliteration of the tympanomastoid cleft has been advocated in patients with cochlear dysplasia and CSF fistula [18,21]. It has also been advocated in intractable cases not responding to continuous lumbar drainage [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the applications of an implanted hearing aid and active middle ear plant can offer correction of conductive and mixed-type hearing losses (3,4). These advantages have repopularized the procedure of "blind sac closure," especially in patients with cavity problems or with unavoidable ear infection despite multiple operations.…”
Section: Introductionmentioning
confidence: 99%